Identification and validation of novel source of resistance to downy mildew in cucumber (Cucumis sativus) - RANJAN, PRAGYA; DEY, SHYAM S; SAGAR, VIDYA; HEGDE, VIVEK; PANDEY, SUDHAKAR; KIRAN, RAJ; PANDEY, CHITHRA DEVI; BAG, MANAS K; DAS, AMRITA; GAWADE, B H; PANDEY, SUSHIL; SINGH, P K; et al. (The Indian Journal of Agricultural Sciences, 2025)
The experiment was conducted during rainy (kharif) season of 2021–2023 under natural epiphytotic conditions at three locations, viz. ICAR-Indian Agricultural Research Institute, New Delhi, ICAR-Indian Institute of Vegetable Research, Varanasi, Uttar Pradesh and ICAR-Indian Institute of Horticultural Research, Bengaluru, Karnataka to identify novel resistance source for downy mildew in cucumber (Cucumis sativus L.). One hundred fifty-six cucumber genotypes including checks were screened. Consequently, a subset of 5 cucumber genotypes showing resistant/ moderately resistant disease reaction at more than one location were selected for validation through multi-location, multi-year testing of their disease response under replicated trial followed by artificial screening. Accessions IC527400 and IC572024 showed field resistance with an average PDI ranging from 11.68–40.39 and 4.08–58.10, respectively at different locations as compared to 37.6–92.9 PDI in susceptible check Pusa Uday. The disease reaction in these genotypes under artificial screening was in accordance with disease reaction under natural conditions. The overall data suggested that IC527400 and IC572024 collected from West Bengal and Lakshadweep, respectively were quite promising as they recorded resistant to moderately resistant reaction at all the three locations and performed better than two of the resistant checks PI 197085 and PI 197086. Even under artificial screening these lines were free from disease symptoms even after 25 days of inoculation. This showed that these lines may have the potential of multi strain/race/pathotype resistance which may be utilized for development of resistant cultivars.